Measuring six facets of curiosity in Germany and the UK: a German-language adaptation of the 5DCR and its comparability with the English-Language source version - Grüning, David; Lechner, Clemens (Journal of personality assessment, 2023)
The five-dimensional curiosity-scale revised (5DCR) by Kashdan et al. (2020) is the most comprehensive curiosity inventory available to date. 5DCR measures six facets of curiosity with four items each. Here, we present a German-language adaptation of the 5DCR and comprehensively validate this adaptation in a diverse sample of adults from Germany (N = 486). Moreover, we provide new evidence on the original English-language 5DCR in a parallel sample from the UK (N = 483). In both countries, we investigate the six facets' reliability, factorial validity, and convergent and discriminant validity with a large set of individual-differences constructs. In addition, we analyze the measurement invariance of the curiosity facets across the UK and Germany and across socio-demographic subgroups defined by age, sex, and education. Findings demonstrate that the new German-language adaptation of 5DCR and its English-language source version show psychometric properties similar to the original studies by Kashdan et al. (2020) in the United States. All six curiosity facets reach at least partial scalar invariance across cultures, sex, education, and mostly also across age groups. The findings support the six-faceted theory of curiosity and show that 5DCR allows for a valid assessment of curiosity across cultures.
Online veröffentlicht: 8. April 2022
Gesehen am 17.09.2024